Haemato-Biochemical Response in Dogs to Ropivacaine Administered via Intraperitoneal Route and Quadratus Lumborum Block for Ovariohysterectomy under Propofol-Diazepam Anaesthesia - Bharali, Moushumi; Bayan, Hitesh; Konwar, Bedanga; Priyaluxmi, Sharungbam; Lalremruati , Joan RC (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Abdominal surgery induces inflammatory responses during the peri and post-operative period in dogs necessitating the incorporation  of effective analgesic strategies. Ropivacaine, an amino amide local anaesthetic is favoured in analgesic protocols due to its lower  cardiotoxicity. This study was conducted to evaluate the haemato-biochemical changes associated with ropivacaine when administered  via intraperitoneal route and quadratus lumborum block in 24 clinical cases of female dogs undergoing ovariohysterectomy. The dogs  were randomly divided into three groups: the control group (Group M), the intraperitoneal group (Group RP), and the quadratus lumborum  group (Group RQ), comprising of 8 dogs in each. Anaesthetic protocol included premedication with IM glycopyrrolate and meloxicam,  followed by IV diazepam, induction achieved with propofol and maintained by continuous infusion of propofol. Haemato-biochemical  parameters were evaluated at 0 min (before premedication), 1 and 24 h after laparotomy incision. Haematological fluctuations were  within the physiological limit throughout the study. Serum creatine kinase remained increased till 24 h; serum cortisol and blood  glucose increased significantly at 1 h; however, the changes were within the physiological limit. These findings suggest that ropivacaine,  administered via either route, provides safe and effective analgesia without significant adverse effects.
Keywords: Dogs; Haemato-biochemical; Intraperitoneal; Quadratus lumborum block; Ropivacaine